2018
DOI: 10.1371/journal.pone.0202505
|View full text |Cite
|
Sign up to set email alerts
|

Role of the circadian clock in the statistics of locomotor activity in Drosophila

Abstract: In many animals the circadian rhythm of locomotor activity is controlled by an endogenous circadian clock. Using custom made housing and video tracking software in order to obtain high spatial and temporal resolution, we studied the statistical properties of the locomotor activity of wild type and two clock mutants of Drosophila melanogaster. We show here that the distributions of activity and quiescence bouts for the clock mutants in light-dark conditions (LD) are very different from the distributions obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The first quantitative analysis of bouts (Penev et al, 1997) already proposed that rest bouts were of two types: short bouts within an activity bout or long bouts between activity bouts. More generally, rest bout lengths appear to follow a power-law (heavy-tailed) distribution in mice, humans and fruit flies (Nakamura et al, 2008;Cascallares et al, 2018) that breakdown under certain pathologies. The rest bout distribution in this study did not show power-law characteristics (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The first quantitative analysis of bouts (Penev et al, 1997) already proposed that rest bouts were of two types: short bouts within an activity bout or long bouts between activity bouts. More generally, rest bout lengths appear to follow a power-law (heavy-tailed) distribution in mice, humans and fruit flies (Nakamura et al, 2008;Cascallares et al, 2018) that breakdown under certain pathologies. The rest bout distribution in this study did not show power-law characteristics (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…2B.I) might be due to larval intrinsic activity rhythms. Adult flies anticipate the light-dark transition phases through their biological clock and increase their activity according to this anticipation 10 . It appears possible that the same activity rhythm pattern might also be true for larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, a powdered sugar yeast food source could be provided in place of the agar and may reduce the risk of contamination. The locomotor activity method has been used successfully with other groups of insects including the study of the circadian rhythms of Drosophila (Diptera; Chiu et al ., ; Cascallares et al ., ), the response of irradiated and nonirradiated light brown apple moth to pheromone and temperature stimuli ( Epiphyas postvittana , Lepidoptera; Brown et al ., ), and may be a useful tool for future probiotic studies with adult tephritids in SIT programs.…”
Section: Discussionmentioning
confidence: 99%